Non-communicable disease care and management in two sites of the Cape Town Metro during the first wave of COVID-19: A rapid appraisal - Peter A. Delobelle; Mumtaz Abbas; Ishaaq Datay; Angela De Sa; Naomi Levitt; Darcelle Schouw; Steve Reid (AOSIS, 2022)
Background: Non-communicable diseases (NCDs), including type-2 diabetes and hypertension, have been associated with increased morbidity and mortality rates because of coronavirus disease 2019 (COVID-19). Maintaining quality care for these conditions is important but data on the impact of COVID-19 on NCD care in South Africa are sparse. Aim: This study aimed to assess the impact of COVID-19 on facility and community-based NCD care and management during the first COVID-19 wave. Setting: Two public health sector primary care sites in the Cape Town Metro, including a Community Orientated Primary Care (COPC) learning site. Methods: A rapid appraisal with convergent mixed-methods design, including semi-structured interviews with facility and community health workers (CHWs) (n = 20) and patients living with NCDs (n = 8), was used. Interviews were conducted in English and Afrikaans by qualified interviewers. Transcripts were analysed by thematic content analysis. Quantitative data of health facility attendance, chronic dispensing unit (CDU) prescriptions and routine diabetes control were sourced from the Provincial Health Data Centre and analysed descriptively. Results: Qualitative analysis revealed three themes: disruption (cancellation of services, fear of infection, stress and anxiety), service reorganisation (communication, home delivery of medication, CHW scope of work, risk stratification and change management) and outcomes (workload and morale, stigma, appreciation and impact on NCD control). There was a drop in primary care attendance and an increase in CDU prescriptions and uncontrolled diabetes. Conclusion: This study described the service disruption together with rapid reorganisation and change management at primary care level during the first COVID-19 wave. The changes were strengthened by the COPC foundation in one of the study sites. The impact of COVID-19 on primary-level NCD care and management requires more investigation.